Unification of Global Hijrah Calendar In Indonesia: An Effort To Preserve The Maqasid Sunnah of The Prophet (SAW) - Abdul Mufid (Journal of Islamic Thought and Civilization, 2020)
This investigation shows the development of the Muslim global calendar from the view point of maqasid-e-sunnah nabawiyah and maqasid-e-shariah. This section investigates maqasid-e-sunnah nabawiyah and maqasid-e-shariah in the framework of the Hijri calendar federalization project in Indonesia. The questions to consider provide the amount need for an interconnected or unified schedule in Indonesia. There are as many as three levels in the Indonesian context. Firstly, the school of pessimism. Secondly, the optimistic school. Thirdly, the high school. As far as the school of pessimism is concerned, people belonging to this school think that creating a global astrolabe (calendar) is like a ridges desire for the surface of the earth. In contrast to the school of pessimism, there is the school of optimism. According to another school of philosophy, Indonesian Muslims must be enthusiastic and should make an attempt to unify the Hijri calendar. Moreover, the middle school believes that the unification of schedules, both locally and globally, is vital. If this task can be completed at once, it will be both effective and valuable. This research is now in the type of a literature review on maqasid and maqasid-e-shariah approaches. The results revealed that based on the assessment of maqasid-e-sunnah and maqasid-e-shariah, something like a single calendar in the Indonesian context did not achieve the urgent (principal) threshold. Even though Muslim people in Indonesia in particular and citizens in general keep living in peace and unity without the need for an integrated Hijri calendar, never to the point of threatening anarchy and chaos. This study suggests that it is wished that the inter-organizational statistics in Indonesia will be capable of taking heart in tackling all aspects of advancement in attempts to unify the Islamic calendar